Sediment quality assessment of the tributaries of the Santos-São Vicente Estuarine System – Brazil - Perina, Fernando Cesar; Torres, Ronaldo José; Mozeto, Antonio Aparecido; Nascimento, Marcos Roberto Lopes; Abessa, Denis Moledo de Souza (Ecotoxicology and Environmental Contamination, 2018)
The Santos-São Vicente Estuarine System has a long history of environmental impacts, and several studies have been performed in this region. However, the quality of its tributaries was not previously studied. This study aimed to investigate the quality of sediments from five rivers (Santana, Mariana, Piaçabuçu, Quilombo, and Diana Rivers) and three sampling sites at Piaçaguera Canal (riverbed, right and left banks), by using an integrated approach involving chemical analyses and whole sediment toxicity tests. Chronic and acute toxicity tests were performed using, respectively, copepods Nitocra sp. and amphipods Tiburonella viscana. The studied sediments presented moderate to high levels of PAHs, PCBs, metals (Cu, Hg, Ni, Pb, Zn), and As. The majority of sediments produced chronic toxic effects, and samples from Piaçaguera Canal were consistently toxic in all acute and chronic tests. The integration of data through multivariate analyses indicated that the toxicity was closely related to the sediments contamination. Chemical data were compared with sediment quality guidelines, which evidenced that the site-specific values are adequate to predict impacts. The levels of organic chemicals and metals suggest constant inputs from diffuse and point sources, demanding actions to ensure effective control and management of the contamination sources to the estuary.